2012
DOI: 10.5251/abjna.2012.3.11.466.475
|View full text |Cite
|
Sign up to set email alerts
|

RAPD analysis of genetic diversity in natural populations of Aegilops geniculata Roth and Triticum durum Desf from Tunisia

Abstract: Aegilops geniculata Roth (Poaceae) is a potential source of genetic variation for wheat improvement. In order to distinguish and evaluate different genetic of Aegilops and Triticum using RAPD markers, thirteen Aegilops geniculata populations and three durum wheat varieties (Triticum durum Desf.) were collected from different regions of Tunisia (North and central).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(26 reference statements)
1
2
1
Order By: Relevance
“…Genetic diversity was high within populations or germplasm types but relatively low between populations. These findings are in accordance with a number of studies (Arora et al 2014;Dashchi et al 2012;Mahjoub et al 2012). The low variability among populations can be explained by the high gene flow value obtained, which is a general indicator of the magnitude of genetic exchange (Abouzied et al 2013), the level of differentiation among the population being inversely proportional to the value of gene flow.…”
Section: Discussionsupporting
confidence: 92%
“…Genetic diversity was high within populations or germplasm types but relatively low between populations. These findings are in accordance with a number of studies (Arora et al 2014;Dashchi et al 2012;Mahjoub et al 2012). The low variability among populations can be explained by the high gene flow value obtained, which is a general indicator of the magnitude of genetic exchange (Abouzied et al 2013), the level of differentiation among the population being inversely proportional to the value of gene flow.…”
Section: Discussionsupporting
confidence: 92%
“…Such a result is expected with regard to the autogamous breeding system of B. distachyon s.l and confirms the lack of inter-crossing pollination (Vogel et al 2009). This finding does not agree with that presented by Filiz et al (2009) using AFLP markers and Turkish natural populations of B. distachyon but is in accordance with that found by Mahjoub et al (2012) in Tunisian natural populations of Aegilops geniculata Roth (Poaceae) using RAPD markers (0·80 of within-population variation) and Ehtemam et al . (2009) in Triticum species in Iran.…”
Section: Discussioncontrasting
confidence: 59%
“…The results of AMOVA, based on SSR markers, revealed a significantly greater within species genetic variation than between species (Table 3). Likewise, a previous study on Aegilops geniculata and Triticum durum showed a greater within species genetic variation than between species (MAHJOUB et al 2012).…”
Section: Discussionmentioning
confidence: 61%